The impact of digital marketing technology for transformation on SMES: a systematic review / Shaherah Abdul Malik, Norria Zakaria and Shahrina Othman - Abdul Malik, Shaherah; Zakaria, Norria; Othman, Shahrina (UiTM Cawangan Johor, 2024)
This comprehensive systematic review delves into the complex landscape of digital marketing adoption within Small and Medium Enterprises (SMEs). By scrutinizing existing literature, it aims to uncover nuanced insights into the multifaceted dynamics surrounding digital marketing strategies in SMEs, emphasizing its impact, challenges, and strategic imperatives for sustainable growth in the digital era. Employing a systematic approach, this review synthesizes various scholarly articles, research reports, and industry insights to unravel the intricate dynamics of digital marketing adoption in SMEs. By meticulously analyzing existing literature, this study seeks to uncover underlying patterns, emerging trends, and critical success factors shaping SIVfEs' digital marketing endeavors. The findings of this systematic review carry profound practical implications for SMEs navigating the complex terrain of digital marketing. By distilling key insights and best practices, this study equips SIVfEs with actionable strategies to optimize their digital marketing efforts, enhance customer engagement, and foster sustainable growth amidst evolving market dynamics. Keywords: Digital marketing, Small and Medium Enterprises (SMEs), Transformation, Data driven decision-making